Warlords, State Failures, and the Rise of Communism in China - Huang, Zhangkai; Miao, Meng; Shao, Yi; Xu, Lixin Colin (World Bank, Washington, DC, 2021)
This paper documents that the spread of communism in China was partly caused by state failures in the early 20th century. It finds that famines became more frequent after China fell into warlord fragmentation, especially for prefectures with less rugged borders and those facing stronger military threat. The relation between topography and famines holds when using historical border changes to instrument border ruggedness. More people from famine-inflicted prefectures died in the subsequent decades for the communist movement, but not for the Nationalist Army. There is evidence that famines exacerbated rural inequality, which pushed more peasants to the side of the communists.